2017
DOI: 10.17265/2161-6256/2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid Content and Antioxidant Properties in Different Extracts of Calluna vulgaris (L.) Flowers

Abstract: This study evaluated the effect of four different solvent, i.e., water, ethanol, water-ethanol mixture and ethyl acetate, on the antioxidant activities of wild and cultivated heather (Calluna vulgaris (L.) Hull) plant. The highest values for total flavonoid content were obtained for samples extracted using ethanol-water mixture and ethyl acetate. Cupric reducing antioxidant capacity (CUPRAC) method, scavenging ability on 1,1-diphenyl-2-pirylhydrazyl radicals (DPPH) radicals and chelating activity on Fe 2+ ions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In addition, it is used as a preventive and therapeutic agent in increased irritability, anxiety, sleep disturbances, and decreased performance, all of which may be owing to its inhibitory effects on monoamine oxidase-A (MAO-A) [10,11]. The carried out pharmacological studies of extracts of the aerial parts of the plant revealed its antioxidant, antiviral, hepatoprotective, cardioprotective, cytotoxic, genoprotective, and antiproliferative effects [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is used as a preventive and therapeutic agent in increased irritability, anxiety, sleep disturbances, and decreased performance, all of which may be owing to its inhibitory effects on monoamine oxidase-A (MAO-A) [10,11]. The carried out pharmacological studies of extracts of the aerial parts of the plant revealed its antioxidant, antiviral, hepatoprotective, cardioprotective, cytotoxic, genoprotective, and antiproliferative effects [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Even though the phytochemical composition of heather is quite well researched [12,[16][17][18][19]29,30], studies on the change in content of the phenolic compounds in various plant organs (leaves, stems, roots, rhizomes, flowers, and seeds) at various stages of ontogenesis did not take place previously. The authors of the studies available to date researched either the seasonal variation in phenolic compound content in a whole aerial part of the plant or in various organs of the plant at one vegetation phase (mainly at the flowering stage).…”
Section: Introductionmentioning
confidence: 99%